Resin Composite Synthesis Reinforced with Banana Tree Fiber with Carboxylic Silica (SiO2-COOH) Addition as a Nanofiller - Damaru, Restu; Novaringga, Adellia; Darmansyah, Darmansyah; Ginting, Simparmin Br. (Indonesian Journal of Chemical Science, 2021)
Banana tree fiber is a natural fiber that has been widely applied to various needs, for example to a mixture of fabrication composite material, carbon film, and so on. To get a strong composite material, special treatment is required by add another material like nanofiller silica carboxyl (SiO2-COOH), then combined with various types of resin, so that the fiber-based composite material has stronger characteristics than fiber carbon, fiberglass, and another high strength material. The purpose of this study was to determine the effect of resin type and nanofiller concentration on the mechanical properties of composites. In this research, a composite resin with banana tree fiber was reinforced with the addition of nanofillers with the variations used namely the type of resin and the concentration of the nanofiller. The best variation in nanofiller concentration is the variation with a concentration of 0.05% w/v in the type of vinyl ester resin. Scanning Electron Microscopy (SEM) shows that nanofiller morphology has been evenly distributed inside the resin matrix. While the tensile strength test using the Ultimate Tensile Machine (UTM) tensile strength test tool Chun Yen 10 kN obtained a tensile strength value of 89.57 MPa and an elongation value of about 1.20%.